Autonomous Growth of a Spatially Localized Supramolecular Hydrogel with Autocatalytic Ability. Issue 34 (7th July 2020) - Rodon Fores, Jennifer; Criado‐Gonzalez, Miryam; Chaumont, Alain; Carvalho, Alain; Blanck, Christian; Schmutz, Marc; Boulmedais, Fouzia; Schaaf, Pierre; Jierry, Loïc
Abstract: Autocatalysis and self‐assembly are key processes in developmental biology and are involved in the emergence of life. In the last decade both of these features were extensively investigated by chemists with the final goal to design synthetic living systems. Herein, we describe the autonomous growth of a self‐assembled soft material, that is, a supramolecular hydrogel, able to sustain its own formation through an autocatalytic mechanism that is not based on any template effect and emerges from a peptide (hydrogelator) self‐assembly. A domino sequence of events starts from an enzymatically triggered peptide generation followed by self‐assembly into catalytic nanofibers that induce and amplify their production over time, resulting in a 3D hydrogel network. A cascade is initiated by traces (10 −18  m ) of a trigger enzyme, which can be localized allowing for a spatial resolution of this autocatalytic buildup of hydrogel growth, an essential condition on the route towards further cell‐mimic designs. Abstract : Towards emergence of life : A domino sequence of events starts from traces of an enzyme triggering peptide generation, which is followed by self‐assembly into catalytic nanofibers that can induce and amplify their own production over time. This self‐sustained cycle leads to an autocatalytic self‐assembled buildup of a hydrogel.